How to Start a 4-H Club (for Youth Ages 8–18) - Keith G. Diem; Joy Jordan; Bryan Terry; Dale Pracht; Judy Butterfield; Adam Cletzer; Lindsey McConnell; Ben Knowles (EDIS)
Being in a 4-H club provides important opportunities for youth to learn subject matter and life skills while working with a caring adult and other youth. Once youth are 4-H members, they become eligible for a variety of the benefits of belonging to 4-H, including awards, trips, and special events. Of course, it’s meant to be fun for the kids and the leaders too! Starting a 4-H club isn’t difficult, and you are encouraged to seek help from parents or other volunteers. Local Extension/4-H staff can help you get started. This 4-page fact sheet was written by Keith G. Diem, Joy Jordan, Bryan Terry, Dale Pracht, Judy Butterfield, Adam Cletzer, Lindsey McConnell, and Ben Knowles, and published by the UF Department of 4-H Youth Development, July 2014.